2017
DOI: 10.1007/s11250-017-1364-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anthelmintic antimicrobial and antioxidant activity of Chenopodium album

Abstract: The objective of this study was to evaluate the anthelmintic, antimicrobial and antioxidant activities of Chenopodium album against gastrointestinal nematodes of sheep and some pathogenic microbes. A worm motility inhibition assay was used for in vitro study, and a faecal egg count reduction assay was used for an in vivo study. Various concentrations ranging from 100 to 500 μg/ml of the extract were subjected to antimicrobial screening by disc diffusion method against four selected bacterial (Staphylococcus au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…With respect to medicinal properties, Salam Jekendra, Joylani, Rebika, & Priyadarshini (2011) observed that C. album extracts exhibited higher antioxidant activity (IC 50 = 206 μg/ml) than vitamin C (IC 50 = 15.1 μg/ml) and quercetin (IC 50 = 6.45 μg/ml). Besides, Lone et al (2017) observed that the extracts of C. album exhibited considerable antimicrobial activity against Staphylococcus aureus, Pseudomonas multocida and Escherichia coli. Moreover, Beyrouthy, Nelly, Annick, and Frederic (2008) have described the use of alcoholic decoctions of aerial parts against rheumatism and arthritis in traditional medicine of Lebanon, while Ksouri et al (2012) have reported unspecified medicinal uses of the species, mostly in the region of Albania.…”
Section: Health Effectsmentioning
confidence: 99%
“…With respect to medicinal properties, Salam Jekendra, Joylani, Rebika, & Priyadarshini (2011) observed that C. album extracts exhibited higher antioxidant activity (IC 50 = 206 μg/ml) than vitamin C (IC 50 = 15.1 μg/ml) and quercetin (IC 50 = 6.45 μg/ml). Besides, Lone et al (2017) observed that the extracts of C. album exhibited considerable antimicrobial activity against Staphylococcus aureus, Pseudomonas multocida and Escherichia coli. Moreover, Beyrouthy, Nelly, Annick, and Frederic (2008) have described the use of alcoholic decoctions of aerial parts against rheumatism and arthritis in traditional medicine of Lebanon, while Ksouri et al (2012) have reported unspecified medicinal uses of the species, mostly in the region of Albania.…”
Section: Health Effectsmentioning
confidence: 99%
“…In the study of Lone et al (2017), DPPH radical scavenging activity of the methanol extracts of C. album ranged from 45% to 73% at concentrations varying from 50 to 300 µg/mL, whereas DPPH radical scavenging activity of the aqueous extracts of C. album ranged from 84% to 96% at concentrations between 50-300 µg/mL (Lone et al, 2017). In our study, DPPH radical scavenging activity of the extracts of C. album ranged from 9.28% to 24.90%.…”
Section: Antioxidant Activitymentioning
confidence: 44%
“…The researchers also stated that essential oils of Thymus strains are highly active disinfectants so they can be used as evaporators, which can be applied against different human pathogenic bacteria and yeasts. Lone et al (2017) showed that methanol extract showed maximum antibacterial action towards S. aureus, while as mild inhibitory effect was revealed against E. coli among the tested strains.…”
Section: Antibacterial Activitymentioning
confidence: 92%
“…The medicinal plants contain various secondary metabolites that exhibit anthelmintic activity [36,37,38]. The plant Chenopodium album plant was earlier reported for its anthelmintic activity [14,15,16]. Nevertheless, the responsible secondary metabolites and their mechanism for anthelmintic activity have never been explored.…”
Section: Discussionmentioning
confidence: 99%
“…[11,12,13]. The plant was reported for its anthelmintic activity [14,15,16]. Nevertheless, the responsible secondary metabolites and their mechanism for anthelmintic activity have never been explored.…”
Section: Introductionmentioning
confidence: 99%